Information retrieval technique using tag-info method for digital DICOM X-ray images - Azrulhizam, Shapi’i; Riza, Sulaiman, Prof. Madya. Ir. Dr.; Anton Satria, Prabuwono, Prof. Madya. Dr.; Mohammad Khatim, Hasan, Prof. Madya. Dr.; Abdul Yazid, Mohd Kassim, Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/